Geomorfología de La Hoya, Cordón Esquel, Noroeste de Chubut - Martínez, Oscar Alfredo (2017)
The depression known as La Hoya (~ l,900 m a.s.l.), located at the southern end of the Esquel Range, was a glacial cirque connected to a valley glacier during the Last Glaciation (Late Pleistocene). Its exceptional size, 3 times the average area of the cirques of the region, would be the consequence of an intense and rapid retreat of the slopes after that main climatic event. This lateral expansion of the boundaries of the original cirque produced an asymmetrical cross profile and would have involved nivation, glacial and periglacial processes, in a context of im- portant generation of detritus. Thus the surface of the depression is largely covered by no less than 35 morpho-sedi- mentary units of different origin, size, age and activity (fossilized and active), which were mapped at l:l0,000 scale, and include rock glaciers, solifluxion lobes and terraces, Protalus rampart, nivation hollows, glacial cirques and remains of marginal moraines. These last assigned, preliminarily, to the Late Glacial event.Most of the sedimentary units identified in this work constitute the recharge and storage area of water for human consumption of the Esquel city and, therefore, it is very important to contribute to the knowledge of the behavior and evolution of them.